AMERICAN CONSUMERISM IDEOLOGY PORTRAYED IN PLANTS VS ZOMBIES VIDEO GAME - MURTI, WAHYU RINARAS WIDYA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Consumerism in American society can not be separeted from their ideology, namely the American Dream (life, liberty, and persuit of happiness).This makes American people have their freedom to live better than othersAmerican society and bring their happiness into reality. Often, happiness satisfiedby material desire that makes American people become consumtive society. Inthis thesis the writer wants to elaborate consumerism in American societyportrayed in Plants vs. Zombies video game. The writer uses cultural studies toanalyze this thesis because it is suitable to analyze American consumerismpotrayed in Plants vs. Zombies video game.Research findings show that rules of this game, Plants vs. Zombies gameare aimed to led the player to keep on plants and upgradaing their plants to defeatthe zombies. Some zombies represent American society. In addition, the zombiesthemselves potray humans desire that is never satisfied. For the next researcher,the writer suggests to analyze this game from different view. The next researchermay use semiotic by focusing on plants and zombies relation. Another choice isanalyzing the characters of plants and zombies character by using psychologicalapproach.Keywords: Culture Studies, America, Consumerism, Game.